A Word to Say: The Story of the Maritime Fishermen's Union - Calhoun, Sue (Nimbus, 1991)
A Word to Say is a penetrating account of how inshore fishermen, most of them Acadian, came together to take control of their industry and their livelihood. Threatened with the loss of their way of life, they fought long and hard to be heard by governments and companies alike. In the process, they saw their union spread from the east coast of New Brunswick to the shores of Nova Scotia and Prince Edward Island. As the only union in the country made up strictly of inshore fishermen, the MFU is unique. Although it has not altered the social fabric of the region, it has played a major role in the momentous changes in the fishery since the mid-1970s. In telling the story, Sue Calhoun gives fishermen more than a word to say. She offers clear insights into the lives of inshore fishermen, so often ignored and taken for granted. Her characters aren't rich. They aren't powerful. Many aren't educated. They are ordinary people who have done extraordinary things. --Publisher's description
Keywords: Fishers; History; Maritime Fishermen's Union; Maritime Provinces; Trade unions